ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHIKREDIT MODAL KERJAPERBANKAN DI PROVINSI KALIMANTAN SELATAN - KRISTIANTO SATRIA SURBAKTI; RUDDY SYAFRUDIN (PPJP Universitas Lambung Mangkurat, 2019)
This study aimed to analyze the factors that influenced the working capital loans banking in the province of South Kalimantan, with independent variables interest rate on working capital loans, inflation rate in South Kalimantan Province, and rates of economic growth in the province of South Kalimantan. This study uses time series data from 2003-2017.The Analysis used are multiple regression with Ordinary Least Square (OLS). The result of this study indicate that the variable interest rates of working capital loans have a significant effect on 5%,while economic growth have significant effect on 10% while inflation do not have the significant effect on working capital loan banking in South Kalimantan Province.Keywords: working capital loans, interest rates on working capital loans, inflation, and rate of economic growth.